Theorizing Intersectionality and Sexuality
XV, 278 p.
Keywords: This book re-examines political, conceptual and methodological concerns of 'intersectionality', bringing these into conversation with sexuality studies. It explores sexual identifications, politics and inequalities as these (dis)connect across time and place, and are re-constituted in relation to class, disability, ethnicity, gender and age.